Tingkat Keramah Lingkungan Penggunaan Alat Tangkap Jaring Tarik Pantai (Beach Seine) di Pantai Prigi Trenggalek Jawa Timur - Tunjung Arum Atmanto; Gilang Rusrita Aida; Achmad Kusyairi (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2025)
Fishing activities at Prigi Beach Trenggalek, East Java are carried out using beach seine nets fishing equipment. This research was conducted at Prigi Beach Trenggalek, East Java on December 11 - December 31 2023. The goal of this research was to determine the level of environmental friendliness of the use of beach seine nets at Prigi Beach Trenggalek, East Java. This research uses a survey method with data collection techniques using the questionnaire interview method. The environmental friendliness level analysis used includes 9 criteria for environmentally friendly fishing gear based on the Code of Conduct for Responsible Fisheries (CCRF). The score obtained from the calculation of the data analysis is 23.96 which means that the use of Beach Seine Nets at Prigi Beach Trenggalek East Java is environmentally friendly.